Think of copper - Jorquera, Daniela; Brancoli , Bernardita (Base Diseño e Innovación, 2015)
The year 2010, Los Pelambres mining and The Museum of Contemporary  Art created a contest called think of copper. The objective: to create a space for new forms of creation and development in the use of the red metal.